PENGGUNAAN TEKNOLOGI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII DI SMP ISLAM TELUKJAMBE KARAWANG: The Use of Technology in Islamic Religious Education Learning for Grade VIII Students at Islamic Junior High School Telukjambe Karawang - Dini Nurbaiti; Iqbal Amar Muzaki; Taufik Mustofa (STAI Ma'had Aly Al-Hikam Malang, 2026)
This article examines the use of gadgets as a source of information literacy for eighth-grade students in Islamic Religious Education (PAI) classes at SMP Islam Telukjambe Barat in Karawang Regency. The article employs a qualitative approach. The research subjects were eighth-grade students, PAI teachers, and the school principal. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive method, which consists of data reduction, data presentation, and conclusion drawing. The results of the study indicate that students utilize gadgets as a source of information literacy regarding PAI learning, although they are still often distracted by digital entertainment. Students’ ability to evaluate and select religious information using gadgets is moderate. That is, some students can distinguish relevant and appropriate information for PAI learning, but they are not yet fully critical in assessing the credibility of sources. The availability of devices, school internet access, and teacher guidance serve as supporting factors. Meanwhile, social media distractions, a lack of supervision, and low religious digital literacy act as inhibiting factors. Artikel ini bertujuan mengkaji pemanfaatan Gadget sebagai sumber literasi informasi siswa kelas VIII dalam pembelajaran Pendidikan Agama Islam (PAI) di Sekolah Menengah Pertama (SMP) Islam Telukjambe Barat Kabupaten Karawang. Artikel menggunakan pendekatan kualitatif. Subjek penelitian adalah siswa kelas VIII, guru PAI, dan Kepala Sekolah. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis dengan metode interaktif Miles dan Huberman yang terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Gadget dimanfaatkan siswa sebagai sumber literasi informasi tentang pembelajaran PAI, meskipun masih sering terdistraksi oleh hiburan digital. Kemampuan siswa dalam mengevaluasi dan memilih informasi keagamaan melalui Gadget berada pada tingkat sedang. Yaitu sebagian siswa mampu membedakan informasi yang relevan dan sesuai dengan pembelajaran PAI, tetapi belum sepenuhnya kritis dalam menilai kredibilitas sumber. Ketersediaan perangkat, akses internet sekolah, dan arahan guru menjadi faktor pendukung. Sedangkan distraksi media sosial, kurangnya pengawasan, dan rendahnya literasi digital keagamaan menjadi faktor penghambat. Kata Kunci : Gadget; Pembelajaran PAI; Pendidikan Agama Islam; Teknologi Pendidikan.